Influência da compactação no colapso de um solo arenoso - Castro, Ana Patrícia Aranha [UNESP] (2016)
Soil compaction is an essential activity in geotechnical works and its proper execution is able to promote significant improvements in soil behavior. Thus, the knowledge of the soil and the control of implementation methods are indispensable for the good performance in work. Variation of soil moisture and, consequently, in soil suction field directly influences their behavior when submitted or not to overloads. The compaction field control is the most viable alternative for improving collapsible soils. Poorly compacted landfill soils can have collapsible behavior when flooded. In this sense, this research is a study of compaction as improvement method for a sandy collapsible soil from the region of Bauru-SP. Characterization tests, Proctor Normal compaction, as well as conventional oedometric tests and controlled suction oedometric tests are part of the research experimental program. From the results obtained, it was found that the collapse settlements increase with lower degree of compaction. The initial soil moisture before the flood also influences the magnitude of soil collapse. Soils with low initial moisture content have greater collapse when they are wet. For the studied soil, collapse settlements are small and almost negligible for soil with degree of compacted of 90%. Tests performed on samples compacted under the same conditions of natural soil compactness demonstrated that the soil deformability is affected by its low density and the collapse can be higher than the ones obtained in the same soil in natural condition. At this work, a more practical representation of the relationship of collapse potential with soil compaction curve is proposed. Thus, it was found that compaction can sufficiently reduce the problems arising from soil collapsibility with some control in process.